Influence of Polyacrylate on Properties of Polyethelene Compositions - Alkhanov, P.Sh.; Bektashi, S.A.; Musayeva, G.H.; Manafov, M.A.; Rajabova, M.C.; Khalilova, S.M.; Jafarov , V.C. (Herald of Azerbaijan Engineering Academy, 2021)
In paper the influence of polyacrylate (as apprete) and mineral fillers on properties of the compositions on the basis of low density polyethylene has been investigated. It has been shown that the properties of filled composites depend on nature of the polymer matrix, on dispersity and quantity of fillers and also on character of the interaction on the boundary surface with the participation of apprete. It has been established that an introduction of apprete into composition of the prepared composition in quantities of 3-5 mass %, the ultimate strength of the obtained composites is essentially increased. In disturbance of optimal conditions and ratio, the exploitation properties of the compositions are deteriorated.